2016
DOI: 10.1371/journal.pone.0155593
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Removal Behavior of Two Biotrickling Filters under Transient Condition and Effect of pH on the Bacterial Communities

Abstract: Although biotrickling filters (BTFs) applied under acidic condition to remove H2S from waste gases have been reported, the removal behavior of the acidic BTF under transient condition which was normal in most industry processes, and corresponding bacterial community have not been thoroughly studied. In the present study, two BTFs were run under neutral (BTFn) and acidic (BTFa) conditions, respectively. The results revealed that the removal performance of BTFa under transient condition was superior to that of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 42 publications
5
7
0
1
Order By: Relevance
“…PCA analysis showed the presence of three different layers (or stratums) in which bacteria were stratified along the length of the BTF on day 538: a lower layer (H/H o : 0.05), a middle layer (H/H o : 0.2), and an upper layer (H/H o : 0.5–0.9). In line this work, microbial stratification has been reported in other studies of biotrickling filters that treat gaseous compounds 36,65,66 . The canonical correspondence analysis (Fig.…”
Section: Resultssupporting
confidence: 85%
“…PCA analysis showed the presence of three different layers (or stratums) in which bacteria were stratified along the length of the BTF on day 538: a lower layer (H/H o : 0.05), a middle layer (H/H o : 0.2), and an upper layer (H/H o : 0.5–0.9). In line this work, microbial stratification has been reported in other studies of biotrickling filters that treat gaseous compounds 36,65,66 . The canonical correspondence analysis (Fig.…”
Section: Resultssupporting
confidence: 85%
“…One of the most extensive studies, from a microbial ecology point of view, is perhaps the one described by Tu et al, (2015) [104]. In this study, two identical bench scale BTFs packed with volcanic rock, seeded with the same inoculum and acclimated for one month under steady state conditions at pH 4.0 (BTFa, a for acidic) or pH 7.0 (BTFn, n for neutral) were compared in terms of operational performance and microbial populations.…”
Section: Aerobic Biofiltrationmentioning
confidence: 99%
“…It has been reported that the bio-degrading activities mainly occurred in the bottom layer of packing bed [11, 18]. As a result, acidification in the bottom layer is more severe, and the growth rates of sulfur-oxidizing microorganisms inhabiting there can be largely reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Here, another method of using combined packing materials was proposed. Previous study found that the bottom bed accounted for major removal of odorous pollutants [11]. However, removal of the upper packing materials from filter bed significantly lowered the overall removal performance of bioreactor.…”
Section: Introductionmentioning
confidence: 99%